Bourdieu, The Body, and Graham's Post-War Dance - Morris, Gay (Edinburgh: Edinburgh University Press, 2001)
RESUMEN: This paper has a two-fold purpose: first, to demonstrate how Pierre Bourdieu's bodily theory might be of use in dance studies and, second, how Bourdieu's ideas, augmented and enlarged by dance theory, can be applied to a specific case. My example is drawn from recent research on the American dance vanguard during the post-World War II period (1945-1960). It focuses on the relationship between the body and the social in Martha Graham's Night Journey (1947).